A nano metal-oxide composite film and preparation method thereof
By using oxide as an oxide as an interface layer to isolation metal particles by using oxide composite film, and to form a "double shell layer" structure through dual metal particles, the problem of destruction and performance degradation of traditional composite materials at high temperatures, realized the realization High -heat stability and improved electrical performance.
Patent Information
- Application Number
- CN202410028779.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-09
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-01-09
AI Technical Summary
Traditional metal and oxide composite materials cause structural damage and performance failure due to the rapid grain growth of metal nanoparticles at high temperatures, and the nanoscale size gradually degrades the performance of the material in long-term applications.
Continuous film composed of nano -grade metal particles and nano -grade oxides, isolate metal particles through oxides as the interface layer to form a stable nanocarium oxide interface layer, prevent metal nanoparticles from moving and convergence at high temperatures, and through double temperature Metal particles form a metal core-metal/oxide "double shell" structure to enhance thermal stability.
The existence of metal nanoparticles is stable at high temperatures, avoiding structural destruction and performance degradation, improving the dynamics and thermodynamic stability of materials, and improving electrical performance.
Smart Images

Figure CN117802451B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and in particular relates to a nano metal-oxide composite film and a preparation method thereof. Background Art
[0002] Nano-metal-oxide composites combine the excellent properties of nanocrystalline metals (grain size less than 100 nm) and oxides, such as high strength, high hardness, excellent catalytic performance of nanocrystalline metals and good high-temperature thermal stability of oxides. Due to the presence of nano-sized metal particles, nano-metal-oxide composites exhibit unique chemical and physical properties and are widely used in many fields such as catalysis, sensing, and optical devices. For example, when gold is subdivided into nanometers, its reactivity changes from inert to highly active, becoming one of the irreplaceable catalysts in many reaction processes. However, many important industrial reactions and applications require catalysts to be exposed to high temperatures or operate under harsh working conditions for a long time. In traditional metal-oxide composite material systems, small-sized metal nanoparticles are usually embedded or loaded in / on the oxide matrix. Due to the high density of interfaces / grain boundaries, metal nanoparticles will experience rapid grain growth at high temperatures, resulting in the destruction of the composite structure and the failure of related properties. This greatly limits the application of metal-oxide composites. In addition, the excellent physical and chemical properties of metal nanoparticles largely rely on the special effects produced by their ultrafine size, especially the surface plasmon effect, which is strongly related to the size and distribution of nanoparticles. However, the nanoscale size also brings certain limitations. The high reactivity and high energy state of metal nanoparticles may lead to unstable chemical composition and surface structure, causing the material to gradually degrade in performance under long-term application conditions.
[0003] In view of the above situation, the present invention provides a novel nano-metal-oxide composite film with a unique interface structure, which combines the optical and electrical properties of metal nanoparticles and the advantages of high strength, high hardness, high temperature resistance, and oxidation resistance of oxides. The composite film is a continuous film composed of nano-scale metal particles and nano-scale oxides, wherein the metal particles are evenly distributed and isolated by the oxide as an interface layer. In the composite film, the metal nanoparticles can exist stably in an extremely fine size, and the composite oxide surrounds the metal nanoparticles to form a stable nano-scale oxide interface layer, so that the metal nanoparticles can still be stably retained in an extremely small size during high-temperature annealing. In addition, the metal nanoparticles can be composed of one or two metal elements, and the element with higher oxygen affinity in the bimetallic particles will be induced by the outer oxide to segregate to the interface between the metal nanoparticles and the oxide, forming a metal core-metal / oxide "double shell" structure with the outer oxide, and at the same time, it serves as a powerful kinetic barrier to hinder the migration and aggregation of metal nanoparticles, which is conducive to enhancing its thermal stability. Nano-metal-oxide composite films of this structure can be formed within a wide range of compositions. As the metal content increases, there is no agglomeration of nanoparticles in the film. Moreover, due to the increase in metal content, charge carriers can tunnel through the oxide interface layer at the interface, thereby improving the electrical properties (resistivity, carrier density, and carrier mobility) of the nano-composite film. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a nano metal-oxide composite film and a preparation method thereof, and prepares a nano metal-oxide film material with high thermal stability.
[0005] The present invention is achieved through the following technical solutions:
[0006] A nano-metal-oxide composite film, which is a continuous film composed of nano-scale metal particles and nano-scale oxides, wherein the metal particles in the composite film are uniformly distributed, and the oxides serve as an interface layer between the metal particles to isolate the metal particles; the chemical formula of the composite film is: x (A n O m ) 1-x , where 0.01≤ x ≤0.91, M is a metal with strong crystallinity, A n O m It is an oxide with high forming energy.
[0007] Furthermore, the metal M having strong crystallinity is any one or two of Au, Ag, Pt, Ir, Pd, Rh, Ni, Cu, or Al.
[0008] Furthermore, the element with stronger oxygen affinity in the bimetallic nanoparticles is segregated at the interface between the metal particles and the oxide, and the metal particles and the oxide form a metal core-metal / oxide "double shell" structure.
[0009] Furthermore, oxide A having high formation energy n O m It is any one of ZrO2, SiO2, Al2O3, MgO, TiO2 or ZnO.
[0010] Furthermore, the size of the metal particles is less than or equal to 100 nm, and the distance between the metal particles is 1-5 nm.
[0011] The present invention also provides a method for preparing the above-mentioned nano metal-oxide composite film, comprising the following steps:
[0012] S1: Place the substrate for attaching the nano-metal-oxide composite film into a beaker, ultrasonically clean it with acetone, alcohol, and deionized water for 10-20 min in sequence, and then blow dry it with a nitrogen gun;
[0013] S2: Place the substrate into the vacuum coating equipment and evacuate the sputtering chamber to 2×10 -4 Pa, the substrate was bombarded with a high-energy Ar + beam for 10 min to remove surface contaminants;
[0014] S3: Fix one / two metal targets and one oxide target in a sputtering chamber, introduce 30 sccm of high-purity argon gas to bombard the targets simultaneously, so that the bombarded metal ions and oxide molecules are deposited on the substrate simultaneously; or
[0015] Three metal targets are fixed, one of which is an active metal target. 30 sccm of argon gas is introduced to bombard the metal target and 20 sccm of oxygen is introduced at the same time, so that the bombarded active metal ions are combined with oxygen ions to form oxide molecules, which are deposited on the substrate at the same time as the metal ions bombarded from other targets.
[0016] Furthermore, in step S3, the metal target is any one or two of Au, Ag, Pt, Ir, Pd, Rh, Ni, Cu or Al; the active metal target is any one of Zr, Al, Mg, Ti or Zn.
[0017] Furthermore, in step S3, the oxide target is any one of ZrO2, SiO2, Al2O3, MgO, TiO2 or ZnO.
[0018] Furthermore, in step S3, the working pressure is 0.6-3 Pa, and the substrate temperature during deposition is 25-100°C.
[0019] Furthermore, in step S3, the metal target during the sputtering process is controlled by DC magnetron sputtering with a power of 1-16 W, and the oxide target is controlled by RF magnetron sputtering with a power of 120-200 W.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] In the traditional metal and oxide composite material system, small-sized metal nanoparticles are usually embedded or loaded in / on the oxide matrix. Due to the high density of grain boundaries / interfaces, metal nanoparticles will experience rapid grain growth at high temperatures, resulting in the destruction of the composite material structure and the failure of related properties. The nano-metal-oxide composite film in the present invention has the following characteristics:
[0022] 1. The nano metal-oxide composite film has very high thermal stability, and its unique interface structure improves the kinetic and thermodynamic stability of the material, allowing the metal nanoparticles to exist stably at high temperatures. The film structure of the nano metal-oxide composite film is not damaged by high temperatures, and the metal nanoparticles contained therein do not agglomerate below 700°C.
[0023] 2. The metal nanoparticles of the nano-metal-oxide composite film are composed of one or two metal elements. The element with stronger oxygen affinity in the bimetallic particles is induced by the oxide to segregate at the interface between the metal nanoparticles and the oxide, forming a metal core-metal / oxide "double shell" structure with the outer oxide, which serves as a powerful kinetic barrier to prevent the migration and aggregation of metal nanoparticles.
[0024] 3. The nano-metal-oxide composite film contains nano-scale metal particles with a size of less than or equal to 100 nm, which can be formed within a wide range of compositions. As the metal content increases, the metal nanoparticles do not agglomerate, have clear outlines, are evenly dispersed, and have improved electrical properties.
[0025] 4. The nano metal-oxide composite film has a high film-forming rate and good adhesion. It can be prepared over a wide temperature range, allowing for the widespread use of a variety of substrates. The composite film has very good repeatability and low production cost, making it suitable for industrial-scale production. It also has ultra-high thermal stability and can be used as a high-temperature resistant coating under harsh industrial conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 : Schematic diagram of the structure of the nano metal-oxide composite film of the present invention;
[0027] Figure 2: TEM images, HRTEM images and particle size distribution images corresponding to Examples 1-3 of the present invention;
[0028] Figure 3 : The Au-SiO2 interface configurations before and after Cu segregation (a) and the segregation energy of Cu at the Au-SiO2 interface (b) corresponding to Examples 1-3 of the present invention;
[0029] Figure 4 : TEM images, HRTEM images and particle size distribution images of Examples 2 and 3 of the present invention respectively after annealing at 400° C. for 1 h;
[0030] Figure 5 : TEM images, HRTEM images and particle size distribution images corresponding to Examples 4-7 of the present invention;
[0031] Figure 6 : TEM images, HRTEM images and particle size distribution diagram of Example 4 of the present invention after annealing at 400°C, 500°C and 600°C for 1 h;
[0032] Figure 7 : TEM image, HRTEM image and particle size distribution diagram of Example 6 of the present invention after annealing at 400°C and 500°C for 1 h respectively;
[0033] Figure 8 : TEM and HRTEM images of Example 8 of the present invention;
[0034] Fig. 9 : HRTEM images of Example 8 of the present invention after annealing at 400°C and 500°C for 1 h;
[0035] Fig.10 : TEM images of the deposited state and particle size distribution diagrams corresponding to Examples 10 and 11 of the present invention, respectively;
[0036] Fig.11 : TEM images and particle size distribution diagrams of Examples 10 and 11 of the present invention after annealing at 500° C. and 600° C. for 1 h, respectively;
[0037] Fig.12 : TEM images of Examples 12 and 13 of the present invention after annealing at 600°C for 1 h. DETAILED DESCRIPTION
[0038] The exemplary embodiments of the present invention will be described in more detail below with reference to the accompanying drawings. Although exemplary embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to be able to fully convey the scope of the present invention to those skilled in the art. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in conjunction with the embodiments.
[0039] The present invention prepares a novel nano-metal-oxide composite film with a unique interface structure. The composite film is a continuous film composed of nano-scale metal particles and nano-scale oxides. The metal particles are evenly distributed, and the oxides serve as an interface layer to separate the metal particles. Figure 1 As shown; the chemical formula of the composite film is: Mx(AnOm)1-x, where M is a metal with strong crystallinity, AnOm is an oxide with high forming energy, and x is the metal M content, 0.01≤ x ≤0.91.
[0040] The metal M having strong crystallinity is any one or two of Au, Ag, Pt, Ir, Pd, Rh, Ni, Cu, and Al.
[0041] The element with stronger oxygen affinity in the bimetallic nanoparticles is segregated at the interface between the metal particles and the oxide. The metal particles form a core / shell structure composed of their own bimetal. The metal particles and the oxide serving as the interface layer between the metal particles form a metal core-metal / oxide "double shell" structure.
[0042] Oxide A with high forming ability n O m It is any one of ZrO2, SiO2, Al2O3, MgO, TiO2 or ZnO.
[0043] The size of the metal nanoparticles in the nano-metal-oxide composite film is less than or equal to 100 nm, the metal nanoparticles are densely and evenly distributed, and the distance between the metal nanoparticles is 1-5 nm.
[0044] The present invention prepares the above-mentioned nano metal-oxide composite film by the following method:
[0045] S1: Cut the substrate for attaching the nano-metal-oxide composite film into 20×20×1 mm 3The size of the substrate was placed in a beaker and ultrasonically cleaned with acetone, alcohol, and deionized water for 10-20 min, and then dried with a nitrogen gun. The substrates used included Si <100> Semiconductor wafers, quartz wafers, metals, oxides, Si3N4 TEM windows.
[0046] S2: Place the substrate into the vacuum coating equipment and use a mechanical pump and a turbomolecular pump to evacuate the sputtering chamber to a vacuum of 2×10 -4 Pa; bombard the substrate with a high-energy Ar+ beam for 10 min to remove surface contaminants; adjust the substrate temperature to 25-100°C through a heating temperature control program with a power of 0-5 A.
[0047] S3: Fix one / two metal targets and one oxide target in the sputtering chamber, with the center of each target forming a 45° angle with the chamber bottom plate. By introducing 30 sccm of high-purity argon gas to bombard the metal and oxide targets simultaneously, the bombarded metal ions and oxide molecules are deposited on the substrate simultaneously. Alternatively, three metal targets are fixed, one of which is an active metal target, and 30 sccm of argon gas is introduced to bombard the metal target while 20 sccm of oxygen is introduced, so that the bombarded active metal ions combine with oxygen ions to form oxide molecules, which are deposited on the substrate simultaneously with the metal ions bombarded from other targets. In this process, the metal target is controlled by DC sputtering with a power of 1-16 W, and the oxide target is controlled by RF sputtering with a power of 120-200 W and a bias voltage of 240-556 V.
[0048] In the above step S3, the purity of the metal target and the oxide target is not less than 99.99 wt.%, the metal target is any one or two of Au, Ag, Pt, Ir, Pd, Rh, Ni, Cu or Al; the oxide target is any one of ZrO2, SiO2, Al2O3, MgO, TiO2 or ZnO. When three metal targets are used for sputtering, the active metal target is any one of Zr, Al, Mg, Ti or Zn.
[0049] After the preparation of the nano metal-oxide composite film, its thermal stability was investigated by heat treatment. The nano metal-oxide composite film has ultra-high thermal stability. Under high temperature conditions of 400-700°C, most of the oxide interface layer is still amorphous, and some oxides will be converted into crystals. There are also cases where amorphous and crystalline layers exist at the same time. However, no matter what the situation is, the oxides can be distributed around the metal nanoparticles to isolate the metal nanoparticles, prevent or effectively slow down the growth of metal nanoparticle grains at high temperatures, and maintain the stability of the composite film structure.
[0050] The present invention prepares a novel nano-metal-oxide composite film with high thermal stability, and its characteristics are further illustrated by the following examples, but the present invention is not limited to the following embodiments. It should be noted that the preparation process of the following embodiments uses a whole block of target material for sputtering. Example 1
[0051] (AuCu) 0.52 (SiO2) 0.48 Nanocomposite film
[0052] Au, Cu and SiO2 are composited by multi-target magnetron co-sputtering to form (AuCu) 0.52 (SiO2) 0.48 Nanocomposite film. The background vacuum degree in the chamber during sputtering is 2.0×10 -4 , the substrate temperature was 25°C. The working pressure was maintained at 0.6 Pa by introducing high-purity argon gas. The substrates to which the films were attached included clean Si wafers (covered with 300 nm amorphous SiO2) and TEM application windows (covered with 10 nm amorphous Si3N4). The Au target and the Cu target were controlled by DC magnetron sputtering, with powers of 16 W and 2 W respectively; the SiO2 target was controlled by RF magnetron sputtering, with a power of 150 W, a total sputtering time of 30 min, and an Ar gas flux of 25 sccm. Figure 2 As shown in the transmission electron microscope (TEM) micrograph in a1, (AuCu) 0.52 (SiO2) 0.48 Gold-copper nanoparticles serve as the core, and amorphous SiO2 serves as the interface layer that isolates the metal nanoparticles. The dark particles are Au-Cu bimetallic nanoparticles, and the bright areas surrounding the metal nanoparticles are amorphous SiO2. The upper right corner is the corresponding selected area diffraction image (SAED), which shows the polycrystalline diffraction ring belonging to fcc. Figure 2 Figure a2 is a high-resolution transmission electron microscope (HRTEM) micrograph, and the inset in the lower right corner is the corresponding fast Fourier transform image (FFT). Figure 2 As shown in the particle size distribution diagram a3, the metal nanoparticles are evenly distributed, with an average size of 2.9 nm, and the distance between the metal particles is about 1-3 nm. Figure 3 As shown in the figure, in the Au-Cu bimetallic particles, the Cu particles are easily induced by SiO2 and aggregated to the interface of Au-SiO2, forming an Au core-Cu / SiO2 "double shell" structure. Example 2
[0053] (AuCu) 0.43 (SiO2) 0.57 Nanocomposite film
[0054] Au, Cu and SiO2 are composited by multi-target magnetron co-sputtering to form (AuCu) 0.43 (SiO2) 0.57 Nanocomposite film. The background vacuum degree in the chamber during sputtering is 1.5×10 -4 , the substrate temperature was 25°C. The working pressure was maintained at 0.6 Pa by introducing high-purity argon gas. The substrates to which the films were attached included clean Si wafers (covered with 300 nm amorphous SiO2) and TEM application windows (covered with 10 nm amorphous Si3N4). The Au target and the Cu target were controlled by DC magnetron sputtering with powers of 5 W and 2 W respectively; the SiO2 target was controlled by RF magnetron sputtering with a power of 150 W, a total sputtering time of 30 min, and an Ar gas flux of 25 sccm. Figure 2 As shown in b1 and b2, (AuCu) 0.43 (SiO2) 0.57 The gold-copper nanoparticles are used as the core, and the amorphous SiO2 is used as the interface layer separating the nanoparticles. Figure 2 As shown in b3, the metal nanoparticles are evenly distributed, with an average size of 2.4 nm, and the distance between the metal nanoparticles is about 1-3 nm. Figure 3 As shown in the figure, in the Au-Cu bimetallic particles, the Cu particles are easily induced by SiO2 and aggregated to the Au-SiO2 interface, forming an Au core-Cu / SiO2 "double shell" structure. Figure 4 As shown in the figure, after annealing at 400℃ for 1 h, the average size of the metal nanoparticles is 2.9 nm, among which the dark particles are Au-Cu nanoparticles, and the bright areas surrounding the metal nanoparticles are amorphous ZrO2. The upper right corner is the corresponding selected area diffraction image (SAED), which shows the polycrystalline diffraction rings belonging to Au. Compared with the pure gold nanofilm prepared under the same conditions, it shows almost stagnant grain growth, showing high thermal stability. Example 3
[0055] (AuCu) 0.35 (SiO2) 0.65 Nanocomposite film
[0056] Au, Cu and SiO2 are composited by multi-target magnetron co-sputtering to form (AuCu) 0.43 (SiO2) 0.57 Nanocomposite film. The background vacuum degree in the chamber during sputtering is 1.0×10 -4, the substrate temperature was 25°C. The working pressure was maintained at 0.6 Pa by introducing high-purity argon gas. The substrates to which the films were attached included a clean Si wafer (covered with 300 nm amorphous SiO2) and a TEM application window (covered with 10 nm amorphous Si3N4). The Au target and the Cu target were controlled by DC magnetron sputtering with powers of 3 W and 2 W respectively; the SiO2 target was controlled by RF magnetron sputtering with a power of 150 W, a total sputtering time of 30 min, and an Ar gas flux of 25 sccm. Figure 2 As shown in c1 and c2, (AuCu) 0.35 (SiO2) 0.65 Gold-copper nanoparticles are used as the core, and amorphous SiO2 is used as the interface layer to separate the nanoparticles. Figure 2 As shown in c3, the metal nanoparticles are evenly distributed, with an average size of 1.9 nm and a distance between the metal particles of about 1-3 nm. Figure 3 As shown in the figure, in the Au-Cu bimetallic particles, the Cu particles are easily induced by SiO2 and aggregated to the Au-SiO2 interface, forming an Au core-Cu / SiO2 "double shell" structure. Figure 4 As shown in the figure, after annealing at 400℃ for 1 h, the average size of the metal nanoparticles is 2.0 nm, among which the dark particles are Au-Cu nanoparticles, and the bright areas surrounding the metal nanoparticles are amorphous SiO2. The upper right corner is the corresponding selected area diffraction image (SAED), which shows the polycrystalline diffraction rings belonging to Au. Compared with the pure gold nanofilm prepared under the same conditions, it shows almost stagnant grain growth, showing high thermal stability. Example 4
[0057] Au 0.49 (ZrO2) 0.51 Nanocomposite film
[0058] Au and ZrO2 were composited by multi-target magnetron co-sputtering to form Au 0.49 (ZrO2) 0.51 Nanocomposite film. The background vacuum degree in the chamber during sputtering is 1.0×10 -4 , the substrate temperature was 25°C. The working pressure was maintained at 0.6 Pa by introducing high-purity argon gas. The substrates to which the film was attached included a clean Si wafer (covered with 300 nm amorphous SiO2), a TEM application window (covered with 10 nm amorphous Si3N4), and a quartz wafer. The Au target was controlled by DC magnetron sputtering with a power of 3 W; the ZrO2 target was controlled by RF magnetron sputtering with a power of 150 W, a total sputtering time of 60 min, and an Ar gas flux of 20 sccm. Figure 5 As shown in the transmission electron microscope (TEM) micrograph in b1, Au 0.49 (ZrO2) 0.51Gold nanoparticles serve as the core, and amorphous ZrO2 serves as the interface layer that separates the gold nanoparticles. The dark particles are gold nanoparticles, and the bright areas surrounding the gold nanoparticles are amorphous ZrO2. The upper right corner is the corresponding selected area diffraction image (SAED), which shows the typical polycrystalline diffraction rings of gold. Figure 5 Figure b2 is a high-resolution transmission electron microscope (HRTEM) micrograph, and the inset in the lower right corner is the corresponding fast Fourier transform image (FFT). Figure 5 As shown in the particle size distribution diagram b3, the gold nanoparticles are evenly distributed with an average size of 3.1 nm, and the distance between the gold nanoparticles is about 1-3 nm. The deposited sample is placed in a quartz tube, and the quartz tube is vacuum-sealed by a tube sealing machine. It is placed in a tube furnace and kept at 400-600°C for 1 h, then quickly cooled in water, and finally the composite film is taken out. After annealing at 400°C, the structure of the composite film does not change, and it is composed of gold nanoparticle cores and amorphous ZrO2 interfaces, and the gold nanoparticles do not grow; after annealing at 500-600°C, although ZrO2 is crystallized, it is still distributed around the gold nanoparticles as an oxide interface layer, inhibiting the coarsening of the gold particles, as shown in FIG. Figure 6 As shown, lattice fringes belonging to t-ZrO2 appear at 500°C. After annealing at 400°C, 500°C, and 600°C for 1 h, the average size of the gold nanoparticles is 3.2 nm, 3.6 nm, and 4.1 nm, which shows almost stagnant grain growth compared with the pure gold nanofilm prepared under the same conditions, showing high thermal stability. Example 5
[0059] Au 0.10 (ZrO2) 0.90 Nanocomposite film
[0060] Au and ZrO2 were composited by multi-target magnetron co-sputtering to form Au 0.10 (ZrO2) 0.90 Nanocomposite film. The background vacuum degree in the chamber during sputtering is 1.5×10 -4 , the substrate temperature was 25°C. The working pressure was maintained at 0.8 Pa by introducing high-purity argon gas. The substrates to which the films were attached included clean Si wafers (covered with 300 nm amorphous SiO2), TEM application windows (covered with 10 nm amorphous Si3N4), and quartz wafers. The Au target was controlled by DC magnetron sputtering with a power of 2 W; the ZrO2 target was controlled by RF magnetron sputtering with a power of 150 W, a total sputtering time of 60 min, and an Ar gas flux of 20 sccm. Figure 5 As shown in a1 and a2, Au 0.10 (ZrO2) 0.90 Gold nanoparticles are used as the core, and amorphous ZrO2 is used as the interface layer to separate the gold nanoparticles. Figure 5As shown in a3, the gold nanoparticles are evenly distributed, with an average size of 2.7 nm, and the distance between the gold nanoparticles is about 3-5 nm. 0.10 (ZrO2) 0.90 The nano-composite film has very high thermal stability. After high-temperature annealing, the surface of the composite film is still dense and smooth, and there is no precipitation of gold particles. The structure of the composite film has not changed. It is composed of a nano-bimetallic particle core and an amorphous / crystalline ZrO2 interface layer, and the nano-gold particles hardly grow. Example 6
[0061] Au 0.85 (ZrO2) 0.15 Nanocomposite film
[0062] Au and ZrO2 were composited by multi-target magnetron co-sputtering to form Au 0.85 (ZrO2) 0.15 Nanocomposite film. The background vacuum degree in the chamber during sputtering is 2.0×10 -4 , the substrate temperature was 25°C. The working pressure was maintained at 0.6 Pa by introducing high-purity argon gas. The substrates to which the films were attached included a clean Si wafer (covered with 300 nm amorphous SiO2), a TEM application window (covered with 10 nm amorphous Si3N4), and a transparent quartz substrate. The Au target was controlled by DC magnetron sputtering with a power of 8 W; the ZrO2 target was controlled by RF magnetron sputtering with a power of 150 W, a total sputtering time of 60 min, and an Ar gas flux of 20 sccm. Figure 5 As shown in c1 and c2, Au 0.85 (ZrO2) 0.15 Gold nanoparticles are used as the core, and amorphous ZrO2 is used as the interface layer to separate the gold nanoparticles. Figure 5 As shown in c3, the gold nanoparticles are evenly distributed, with an average size of 5.5 nm, and the distance between the gold nanoparticles is about 1-2 nm. The deposited sample is placed in a quartz tube, which is vacuum-sealed by a tube sealer, placed in a tube furnace, and kept at 400℃ and 500℃ for 2 h, then taken out and quickly cooled in water, and finally the composite film is taken out. This material has ultra-high thermal stability, such as Figure 7 As shown in the figure, after high temperature annealing at 400°C and 500°C, the structure of the composite film did not change, and it was composed of nano-gold particle cores and amorphous ZrO2 interface layers. After annealing at 400°C and 500°C for 1 h, the average size of the gold nanoparticles was 6.9nm and 8.0 nm; compared with the pure gold nanofilm prepared under the same conditions, it showed very slow grain growth and high thermal stability. Example 7
[0063] Au 0.91 (ZrO2)0.09 Nanocomposite film
[0064] Au and ZrO2 were composited by multi-target magnetron co-sputtering to form Au 0.91 (ZrO2) 0.09 Nanocomposite film. The background vacuum degree in the chamber during sputtering is 1.0×10 -4 , the substrate temperature was 25°C. The working pressure was maintained at 2.0 Pa by introducing high-purity argon gas. The substrates to which the films were attached included a clean Si wafer (covered with 300 nm amorphous SiO2), a TEM application window (covered with 10 nm amorphous Si3N4), and a transparent quartz substrate. The Au target was controlled by DC magnetron sputtering with a power of 16 W; the ZrO2 target was controlled by RF magnetron sputtering with a power of 150 W, a total sputtering time of 60 min, and an Ar gas flux of 30 sccm. Figure 5 As shown in d1 and d2, Au 0.91 (ZrO2) 0.09 Gold nanoparticles are used as cores, and amorphous ZrO2 is used as the interface layer to separate the gold nanoparticles. The gold nanoparticles are evenly distributed, with an average size of 6.6 nm, and the distance between the gold nanoparticles is about 1-2 nm. The material has ultra-high thermal stability. The deposited sample is placed in a quartz tube, and the quartz tube is vacuum-sealed by a tube sealing machine. It is placed in a tube furnace and kept at 400 and 500°C for 2 hours, respectively, and then taken out and quickly cooled in water. The structure of the composite film has not changed, and it is composed of nano-gold particle cores and amorphous / crystalline ZrO2 interface layers. After annealing at 400°C and 500°C for 2 hours, the average size of the gold nanoparticles is 6.9 nm and 7.5 nm. Compared with pure gold nanofilms prepared under the same conditions, Au 0.91 (ZrO2) 0.09 The nanocomposite films showed very slow grain growth and exhibited high thermal stability. Example 8
[0065] (AuAl) 0.5 (MgO) 0.5 Nanocomposite film
[0066] Au, Al and MgO are composited by multi-target magnetron co-sputtering to form (AuAl) 0.5 (MgO) 0.5 Nanocomposite film. The background vacuum degree in the chamber during sputtering is 1.0×10 -4, the substrate temperature is 50°C. The working pressure is maintained at 1.0 Pa by introducing high-purity argon gas. The substrates to which the film is attached include a clean Si wafer (covered with 300 nm amorphous SiO2), a TEM application window (covered with 10 nm amorphous Si3N4) and a transparent quartz substrate. The Au target and the Al target are controlled by DC magnetron sputtering with powers of 3 W and 2 W, respectively; the MgO target is controlled by RF magnetron sputtering with a power of 150 W, a co-sputtering time of 30 min, and an Ar gas flux of 30 sccm. Figure 8 As shown, (AuAl) 0.5 (MgO) 0.5 The gold-aluminum bimetallic nanoparticles are used as the core, and the amorphous MgO is used as the interface layer to separate the metal nanoparticles. The metal nanoparticles are evenly distributed, with an average size of 4.3 nm, and the distance between the metal nanoparticles is about 2-3 nm. The material has ultra-high thermal stability. After high-temperature annealing, the surface of the composite film is still dense and smooth, without particle precipitation; and the structure of the composite film does not change, consisting of nanoparticles and amorphous / crystalline MgO interface layers, and the nanoparticles grow slowly. Example 9
[0067] Au 0.5 (TiO2) 0.5
[0068] Au was composited with TiO2 by reactive magnetron co-sputtering to form Au 0.5 (TiO2) 0.5 Nanocomposite film. The background vacuum degree in the chamber during sputtering is 1.5×10 -4 , the substrate temperature was 75°C. The working pressure was maintained at 3.0Pa by introducing high-purity argon gas. The substrates to which the film was attached included a clean Si wafer (covered with 300 nm amorphous SiO2), a TEM application window (covered with 10 nm amorphous Si3N4), and a transparent quartz substrate. The Au target and the Ti target were controlled by DC magnetron sputtering, with powers of 3 W and 120 W, respectively, an Ar gas flow rate of 30 sccm, an O2 flow rate of 20 sccm, and a total sputtering time of 30 min. Fig. 9 As shown, Au 0.5 (TiO2) 0.5Gold nanoparticles are used as cores, and amorphous TiO2 is used as the interface layer to separate the gold nanoparticles. The gold nanoparticles are evenly distributed, with an average size of 3.3 nm, and the distance between the gold particles is about 2-3 nm. The deposited sample is placed in a quartz tube, and the quartz tube is vacuum-sealed by a tube sealing machine. It is placed in a tube furnace and kept at 400℃ and 500℃ for 1 hour, respectively, and then taken out and quickly cooled in water, and finally the composite film is taken out. This material has ultra-high thermal stability. After high-temperature annealing, the surface of the composite film is still dense and smooth, without the precipitation of gold particles; and the structure of the composite film has not changed, and it is composed of nano-gold particle cores and amorphous / crystalline TiO2 interface layers. After annealing at 400℃ and 500℃ for 1 hour, the average size of the nanoparticles is 4.2 nm and 4.9 nm. Compared with pure gold nanofilms prepared under the same conditions, Au 0.5 (TiO2) 0.5 The nanocomposite films showed almost arrested grain growth, demonstrating high thermal stability. Example 10
[0069] Pt 0.11 (Al2O3) 0.89 Nanocomposite film
[0070] Pt was composited with Al2O3 by multi-target magnetron co-sputtering to form Pt 0.11 (Al2O3) 0.89 Nanocomposite film. The background vacuum degree in the chamber during sputtering is 1×10 -4 , the substrate temperature is 100°C. The working pressure is maintained at 2.0 Pa by introducing high-purity argon gas. The substrates to which the films are attached include a clean Si wafer (covered with 300 nm amorphous SiO2), a TEM application window (covered with 10 nm amorphous Si3N4), and a transparent quartz substrate. The Pt target is controlled by DC magnetron sputtering with a power of 3 W; the Al2O3 target is controlled by RF magnetron sputtering with a power of 120 W, a co-sputtering time of 20 min, and an Ar gas flux of 30 sccm. Fig.10 As shown, Pt 0.11 (Al2O3) 0.89 Pt nanoparticles are used as cores, and amorphous Al2O3 is used as the interface layer to separate the metal nanoparticles. The metal nanoparticles are evenly distributed, with an average size of 1.3 nm, and the distance between the metal nanoparticles is about 2-3 nm. The deposited sample is placed in a quartz tube, and the quartz tube is vacuum-sealed by a tube sealing machine. It is placed in a tubular furnace and kept at 500°C and 600°C for 1 hour, then taken out and quickly cooled in water, and finally the composite film is taken out. This material has ultra-high thermal stability, and the structure of the composite film has not changed. It is composed of nano Pt particle cores and amorphous Al2O3 interface layers, such as Fig.11As shown. After annealing at 500℃ and 600℃, the average size of the metal nanoparticles is 1.3 nm and 1.3 nm. Compared with the pure Pt nanofilm prepared under the same conditions, the Pt 0.11 (Al2O3) 0.89 The nanocomposite films showed almost arrested grain growth, demonstrating very high thermal stability. Embodiment 11
[0071] Pt 0.10 (SiO2) 0.90 Nanocomposite film
[0072] Pt was composited with SiO2 by multi-target magnetron co-sputtering to form Pt 0.10 (SiO2) 0.90 Nanocomposite film. The background vacuum degree in the chamber during sputtering is 2.0×10 -4 , the substrate temperature was 25°C. The working pressure was maintained at 1.0 Pa by introducing high-purity argon gas. The substrates to which the films were attached included a clean Si wafer (covered with 300 nm amorphous SiO2), a TEM application window (covered with 10 nm amorphous Si3N4), and a transparent quartz substrate. The Pt target was controlled by DC magnetron sputtering with a power of 7 W; the SiO2 target was controlled by RF magnetron sputtering with a power of 150 W, a total sputtering time of 17 min, and an Ar gas flux of 25 sccm. Fig.10 As shown, Pt 0.10 (SiO2) 0.90 Pt nanoparticles are used as cores, and amorphous SiO2 is used as the interface layer to isolate the metal nanoparticles. The metal nanoparticles are evenly distributed, with an average size of 1.5 nm, and the distance between the metal nanoparticles is about 1-2 nm. The deposited sample is placed in a quartz tube, and the quartz tube is vacuum-sealed by a tube sealing machine. It is placed in a tube furnace and kept at 500°C and 600°C for 1 hour, then taken out and quickly cooled in water, and finally the composite film is taken out. This material has ultra-high thermal stability, and the structure of the composite film has not changed. It is composed of nano Pt particle cores and amorphous SiO2 interface layers, such as Fig.11 As shown. After annealing at 500℃ and 600℃, the average size of the nanoparticles is 1.6 nm and 2.5 nm. Compared with the pure Pt nanofilm prepared under the same conditions, the Pt 0.10 (SiO2) 0.90 The nanocomposite films show very slow grain growth and exhibit very high thermal stability. Example 12
[0073] Pt 0.01 (SiO2) 0.99 Nanocomposite film
[0074] Pt was composited with SiO2 by multi-target magnetron co-sputtering to form Pt 0.01 (SiO2) 0.99 Nanocomposite film. The background vacuum degree in the chamber during sputtering is 1.0×10 -4 , the substrate temperature was 50°C. The working pressure was maintained at 0.6 Pa by introducing high-purity argon gas. The substrates to which the films were attached included a clean Si wafer (covered with 300 nm amorphous SiO2), a TEM application window (covered with 10 nm amorphous Si3N4, and a transparent quartz substrate. The Pt target was controlled by DC magnetron sputtering with a power of 1 W; the SiO2 target was controlled by RF magnetron sputtering with a power of 150 W, a total sputtering time of 17 min, and an Ar gas flux of 22.3 sccm. Fig.12 As shown, Pt 0.01 (SiO2) 0.99 It has a unique structure with Pt nanoparticles as metal cores and amorphous SiO2 as an interface layer separating the metal nanoparticles. The metal nanoparticles are evenly distributed with an average size of 1.40 nm, and the distance between the metal nanoparticles is about 1-2 nm. The deposited sample is placed in a quartz tube, and the quartz tube is vacuum-sealed by a tube sealing machine. It is placed in a tube furnace and kept at 600℃ and 700℃ for 1 h, then taken out and quickly cooled in water, and finally the composite film is taken out. This material has ultra-high thermal stability, and the structure of the composite film has not changed. It is composed of nano Pt particle cores and amorphous SiO2 interface layers. After annealing at 600℃ and 700℃ for 1 h, the average size of the nanoparticles is 1.4 nm and 1.7 nm. Compared with pure Pt nanofilms prepared under the same conditions, Pt 0.01 (SiO2) 0.99 The nanocomposite films show very slow grain growth and exhibit very high thermal stability. Embodiment 13
[0075] Ag 0.05 (ZnO) 0.95 Nanocomposite film
[0076] Ag and ZnO were composited by multi-target magnetron co-sputtering to form Ag 0.05 (ZnO) 0.95 Nanocomposite film. The background vacuum degree in the chamber during sputtering is 1.0×10 -4, the substrate temperature was 25°C. The working pressure was maintained at 0.6Pa by introducing high-purity argon gas. The substrates to which the films were attached included a clean Si wafer (covered with 300 nm amorphous SiO2), a TEM application window (covered with 10 nm amorphous Si3N4), and a transparent quartz substrate. The Ag target was controlled by DC magnetron sputtering with a power of 2 W; the ZnO target was controlled by RF magnetron sputtering with a power of 150 W, a total sputtering time of 14 min, and an Ar gas flux of 25.8 sccm. Fig.12 As shown, Ag 0.05 (ZnO) 0.95 The Ag nanoparticles are used as the core, and the amorphous ZnO is used as the interface layer to separate the metal nanoparticles. The metal nanoparticles are evenly distributed, with an average size of 1.45 nm, and the distance between the metal nanoparticles is about 1-2 nm. The deposited sample is placed in a quartz tube, and the quartz tube is vacuum-sealed by a tube sealing machine. It is placed in a tube furnace and kept at 400℃ and 500℃ for 1 h, then taken out and quickly cooled in water, and finally the composite film is taken out. This material has ultra-high thermal stability, and the structure of the composite film has not changed. It is composed of nano-Ag particle cores and amorphous ZnO interface layers. After being kept at 400℃ and 500℃ for 1 h, the average size of the nanoparticles is 1.6 nm and 1.8 nm. Compared with pure Ag nanofilms prepared under the same conditions, Ag 0.05 (ZnO) 0.95 The nanocomposite films show very slow grain growth and exhibit very high thermal stability.
[0077] The present invention prepares a novel nano-metal-oxide composite material, which has a unique interface structure and is a continuous film composed of nano-scale metal particles and nano-scale oxides. The metal particles are evenly distributed and isolated by oxides as an interface layer. The metal nanoparticles are composed of one or two metal elements. The element with stronger oxygen affinity in the bimetallic nanoparticles is induced by the outer oxide to segregate at the interface between the metal nanoparticles and the oxide, and forms a metal core-metal / oxide "double shell" structure with the outer oxide. The composite film can be formed in a wide range of components, and as the metal content increases, the metal nanoparticles do not agglomerate, but are evenly distributed, with a size of less than or equal to 100 nm, and the distance between the metal nanoparticles is about 1-5 nm. The nano-metal-oxide composite film has ultra-high thermal stability, and the metal nanoparticles hardly grow at high temperatures, and can be used as a high-temperature resistant coating under harsh working conditions. In addition, the composite film has very good repeatability, low production cost, and is suitable for industrial-scale production.
Claims
1. A nano metal-oxide composite film, characterized in that: The composite film is a continuous film composed of nano-scale crystalline metal particles and nano-scale amorphous oxide. The crystalline metal particles in the composite film are evenly distributed, and the amorphous oxide serves as an interface layer between the crystalline metal particles to isolate the crystalline metal particles. The chemical formula of the composite film is: x (A n O m ) 1-x , where 0.01≤ x ≤0.91, M is a metal with strong crystallinity, specifically any one or two of Au, Ag, Pt, Cu or Al, A n O m The composite film is an oxide with high forming energy, specifically any one of ZrO2, SiO2, Al2O3, MgO or ZnO. The composite film can still maintain its structural stability under high temperature conditions of greater than 400°C and less than or equal to 700°C.
2. The nano metal-oxide composite film according to claim 1, characterized in that: The element with stronger oxygen affinity in the bimetallic nanoparticles is segregated at the interface between the crystalline metal particles and the amorphous oxide, and the crystalline metal particles and the amorphous oxide form a metal core-metal / oxide "double shell" structure.
3. The nano metal-oxide composite film according to claim 1, characterized in that: The size of the crystalline metal particles is less than or equal to 100 nm, and the distance between the crystalline metal particles is 1-5 nm.
Citation Information
Patent Citations
Oxide-metal composite nanoglass material
CN110983270A